(Effect of variety and dosage of mycorrhiza on the growth and yield of pepper plants (Capsicum annuum L.) in Andisol) - Mizan Maulana; Syafruddin Syafruddin; Elly Kesumawati (Jurnal Ilmiah Mahasiswa Pertanian, 2016)
Effect of variety and dosage of mycorrhiza on the growth and yield of pepper plants (Capsicum annuum L.) in Andisol. This study aims to determine the effect of varieties and doses of mycorrhiza on the growth and yield of pepper plants on land Andisol and the interaction between these two factors. This research was conducted at the experimental garden in plant physiology laboratory university agricultural Faculty Syiah Kuala start of June 2015 until December 2015. Research using Random Group 4x3 factorial design with three replications, consisting of 36 experimental units consisting of two factors. he first factor is the dose mycorhiza consists of 4 levels of 0, 5, 10 and 15 g / plant. The second factor varieties consisting of Carlos F1, F1 Kiyo, and La Odeng. The results showed that variety significant effect on yield of pepper plants. The best varieties are varieties Kiyo F1 on the generative phase that can be seen from the weight of the fruit crop age parameter 110 HST and 45 HST mycorhiza infection. While the dose of mycorrhizal significant effect on the growth and yield of pepper plants on land Andisol. Dose best mycorrhiza contained in 10g / plants that can be seen in the number of fruit crops as well as the parameters of mycorhiza infection most. Research also shows there is a higher interaction on Carlos F1 varieties with a dose of 15 g / plant in the parameters the number of leaf age 15 HST, At the age of 30 HST rod diameter also gives the best result in two different varieties, namely in Carlos F1 hybrid varieties and local varieties La Odeng on mycorrhizal dose of 15 g / plant and root infection aged 45 HST. La Odeng varieties give the highest number of mycorrhizal infection in mycorrhizal dose of 10 g / plant.